2000
DOI: 10.1006/jtbi.2000.2160
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sex Ratios in Structured Populations

Abstract: In this paper, we develop a general method to determine evolutionary equilibrium sex ratios and to check evolutionary stability, continuous stability and invadability in exact genetic models with or without dominance. This method is then applied to three kinds of models for structured populations: the "rst one concerns Hamilton's LMC model, except that only a fraction of female o!spring mate with male o!spring born in the same colonies, while a fraction 1! mate with male o!spring chosen at random within the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…A strategy is NIS when selection favours it to replace other strategies. If equations (2.2) and (3.2) hold, Courteau & Lessard (2000) show that…”
Section: Stability Conceptsmentioning
confidence: 99%
“…A strategy is NIS when selection favours it to replace other strategies. If equations (2.2) and (3.2) hold, Courteau & Lessard (2000) show that…”
Section: Stability Conceptsmentioning
confidence: 99%
“…The second term (P i − M i ) is weighted by the fraction of female carriers (1 − M i ). Thus, the dynamics of parameter M i (9) is determined by the action of female carriers of strategy P i as well as partners of male carriers of this strategy in a tug of war mechanism, which means that the activity of female carriers (the second term) attracts M i to the value encoded by the gene P i and the action of partners of male carriers (the first term) attracts M i to the value of the females' average strategyP pr . In [4], it was shown that for P i ∈ (0, 1] a unique attracting nullcline exists within the interval P pr , P i .…”
Section: Details Of the Modelmentioning
confidence: 99%
“…Figure 1 shows the trajectories of the gene frequency dynamics (8) and the respective trajectories of the carrier sex ratio dynamics (9). The dynamics of gene frequencies is determined by the underlying dynamics of the carriers' sex ratios and the secondary sex ratio, according to the rules (10).…”
Section: Lemma 2 (A) For M I and The Current Value Ofp Pr The Dynammentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we are aware, the first authors to derive local invadability properties directly from the characteristic polynomial of the linearised invasion dynamics were Taylor and Bulmer (1980). Their calculations were taken further by Courteau and Lessard (2000). As these techniques are extremely useful in applications we summarise here their extension to higher dimensional trait spaces.…”
Section: Local Theorymentioning
confidence: 99%